SISTEM PENDIDIKAN LANGGAR DI DESA SUNGAI DURIAN KECAMATAN BANUA LAWAS KABUPATEN TABALONG (POTRET PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN MASYARAKAT DESA) - Nabilah, Gina; Rabi'ah, Rabi'ah; Rahmi, Syamsul (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
The Langgar education system was established earlier than schools, pesantren and madrasah. The Langgar education system has taken a very important role in preparing the next generations by being equipped with Islamic religious knowledge. The Langgar education system is part/component of the educational process. The offending education system in this study includes educators, students, offending educational goals, offending educational materials, offending education methods, and offending education evaluation. This research is a field research with qualitative data types. in the design of a portrait study of Islamic religious education in rural communities. Data were collected by interview, observation and documentation techniques. The data processing uses data reduction, data display and data verification. Then analyzed using descriptive qualitative method. This study uses educational factor theory as an analytical tool. The results of this study can be concluded that the education system of Langgar Darul Akhyar in Sungai Durian Village, Banua Lawas District, Tabalong Regency is illustrated in the following description: 1) Langgar Darul Akhyar educators are alumni of Islamic boarding schools and some are even alumni of the Middle East, and some are already at Strata 1 (S1 Arabic). 2) Students who study at Langgar Darul Akhyar are of various ages. 3) Langgar Darul Akhyar education aims to make the community understand religion. 4) Langgar Darul Akhyar educational materials studied, such as the reading of the Hidayatussalikin Book which includes the science of divinity/monotheism, the science of worship/fiqh, the science of cleansing the heart/tasawuf and the reading of the Book of Aqidatul Awwam which includes the science of theology/monotheism. 5) The Darul Akhyar Langgar Education Method is the lecture method and the practical method. 6) Evaluation is never done.